PERAN GURU DALAM MENANAMKAN NILAI AGAMA MELALUI METODE BERCERITA BERGAMBAR DI TK TUNAS HARAPAN NAGORI WONOREJO KECAMATAN PEMATANG BANDAR KABUPATEN SIMALUNGUN - Indi Dwi Utami; Yanti Ansari; Muhammad Wahyudi (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Every early childhood must experience various stages of development in life, from several kinds of development, one of which is the development of religious and moral values. The modernization of the times has an impact on decreasing awareness about the importance of religious values for children. So, to instill religious values themselves, it is necessary to get used to it from an early age. storytelling method in the effectiveness of learning in the cultivation of religious values in early childhood, The implementation of the storytelling method in the cultivation of religious values in early childhood is based on facts in the field related to the condition of children at this time. The purpose of this study was to determine how effective the process of implementing storytelling methods is in increasing religious values in early childhood and to find out how much the results of increasing the development of children's religious values. The data collection techniques used are observation, interview and documentation methods. The application of this storytelling method can use various types of media such as dolls, illustrations, pictures, or other media to attract children's own interests. The process of implementing the storytelling method is carried out in learning and habituation activities.